"I'm Giving You a Lawful Order": Dialogic Legitimacy in Sandra Bland's Traffic Stop. Issue 2 (June 2017) - Lowrey‐Kinberg, Belén V.; Sullivan Buker, Grace
Abstract : On July 10, 2015, a young African American woman named Sandra Bland was stopped by State Trooper Officer Brian Encinia for failing to signal a lane change. What began as a routine traffic stop quickly devolved into shouting, a physical confrontation, and Bland's subsequent arrest. We use discourse analysis to examine the rapid escalation of this encounter with a focus on procedural justice (Sunshine & Tyler2003 ) and the dialogic approach to legitimacy (Bottoms & Tankebe2012 ). In analyzing the transcript of Sandra Bland's traffic stop, we address several key questions: How is procedural justice manifested linguistically? Can the dialogic legitimacy framework be used to understand the dynamics of individual police‐citizen interactions? The conclusions of this analysis provide an interdisciplinary view of how procedural justice and legitimacy are manifested and negotiated in a police‐citizen interaction.